Modeling and design of a three-degree-of-freedom permanent magnet spherical actuator - Yan, Liang (2008)
This thesis focuses on modeling, design and experimental investigation of this proposed PM spherical actuator. Based on the PM poles pattern on the rotor, the magnetic field distribution surrounding the rotor is formulated using Laplace’s equations. Magnetic scalar potential is obtained according to the magnetic properties of rotor materials.